Minutes of the CCAFS 6th Independent Steering Committee Meeting, 25-27 September 2019 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
In September 2019 the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) held its 6th virtual Independent Steering Committee meeting.